Tingkat Kepedulian Sosial Siswa Berbasis Gender - Fitri, Tesya Dilhaya (Jurnal Aplikasi IPTEK Indonesia, 2024)
Social care needs to be enhanced to solve social problems that occur in students. The study described the level of social concern of students in the environment of Global Solar Independent SMK based on a gender survey. This study uses a quantitative approach with descriptive methods. The population in this study was all XI class students totaled 95 students. The sample used was 95 students, sampling technique using saturated samples. The data collection technique is carried out using the likert model scale instrument. The results of this study revealed that SMK Global Solar Independent students have a social concern for their surrounding environment in a moderate category. The data showed that 15.8% had a high social concern, 63.2% had a moderate student social care, and 21.1% had a low student social concern. Then based on gender on average, the level of social attention of female students is higher than that of females